Perencanaan optimalisasi lapangan Letda Made Pica sebagai ruang terbuka hijau publik Kota Denpasar - Dharmadiatmika I Made Agus; Cokorda Gede Alit Semarajaya; Ni Luh Putu Arya Yunita Mahayani (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
The environmental degradation in urban areas can not be separated from the reduced space that can support urban ecology. The availability of urban green open space is very important, especially in the city of Denpasar. One of them is the Letda Made Pica field which is located at Jalan Tukad Nyali, Sanur Kaja Village, South Denpasar District, Denpasar City, Bali. This field is generally used for sports activities such as jogging, running, and football. Seeing the many activities that occur on the site, apart from being a sport field, this area also has the potential to be developed into a new recreational facility. This study uses observation, interviews, and literature study methods with the stages of data inventory, analysis, synthesis, basic concepts, development concepts, and planning. The addition of several supporting facilities for football matches, public facilities, and vegetation throughout the area was carried out to support the function of Letda Made Pica field as a sports field and recreational facility. Several recommendations in the form of perspective drawings are given to provide an overview of the results of the optimalization plan.